Catalytic Carboxylation of Heteroaromatic Compounds: Double and Single Carboxylation with CO2 - Mita, Tsuyoshi; Masutani, Hiroki; Ishii, Sho; Sato, Yoshihiro (Synlett, 2019)
In the presence of PdCl2[P(n-Bu)3]2 (10 mol%) and ZnEt2, 2-furyl and 2-pyrrolylmethyl acetate were carboxylated with CO2 (1 atm), affording doubly carboxylated products in good yields. In this dearomative transformation, α,ε-dicarboxylic acids were obtained selectively, in contrast to our previous report in which α,γ-dicarboxylic acids were selectively produced from 2-indolylmethyl acetates. In contrast, 5-thiazolylmethyl acetate and naphthylmethyl acetates predominantly underwent single carboxylation.
Keywords: carboxylation; CO2; dearomatization; palladium; furan; pyrrole